The Influence Of Rubber Prices On The Income Of Rubber Farmers In Payaraman West District Ogan Ilir District - M. Vilza Raihan Fahrezi; Hilda Hilda; Aryanti Aryanti (Al-Hijrah: Journal of Islamic Economics And Banking, 2024)
This research aims to investigate the influence of rubber prices on economic activity and community welfare in Payaraman Barat Village, Ogan Ilir Regency. The study utilizes a data collection method through a Likert Scale questionnaire. The population in this research includes all rubber farmers, totaling 320 households. The sample is determined using Purposive Sampling technique with the Slovin formula, resulting in a sample size of 77 individuals for this study. Data analysis is conducted using classical assumption tests and simple linear regression analysis. From the research results, it was found that the t-value (2.310) is greater than the t-table value (0.2242), with a significance level of 0.024. Since the significance value of t (0.024) is less than 0.05, it can be concluded that rubber prices have a significant influence on the income of rubber farmers in Payaraman Barat Village, Ogan Ilir Regency.